Development of strength endurance in freestyle wrestlers at the stage of sports specialization - Kolinenko, E. A.; Khandamaev, A.O. (Bulletin of Izvestiya Tula State University. Physical culture. Sport, 2022)
It has been established that the improvement ,of sports training of freestyle wrestlers is influenced by the development of special physical qualities, on the basis of which the level of activity of conducting competitive fights increases. Complexes of exercises have been developed with the inclusion of the CrossFit training system in order to develop the strength endurance of athletes at the stage of sports specialization, which contributes to the success of performing technical actions in attacking techniques. The dynamics of indicators of development of strength endurance in the studied groups is shown.